Innate immunity to retroelements by human AID/APOBEC3 proteins - Harris, Reuben (Henry Stewart Talks, 2007)
Nucleic acid basics, AID-related APOBEC3 proteins are DNA cytosine deaminases, Retrovirus (e.g. HIV and MLV) restriction by APOBEC3 proteins, Endogenous retroelement (e.g. Ty1 and L1) restriction by APOBEC3 proteins, Multifunctionality of AID in diversifying antibody genes and in restricting retroelements